Micro family finances and savings rates: A Strategic Vision - Armendáriz Lasso, Enrique; Arteaga Estrella, Yadira (Revista Universidad de Guayaquil, 2013)
In research conducted 91% of the sample estimates to exploit their potential savings and entrepreneurship are a powerful duo in the fight against poverty, lack of employment and growth, is a way to strengthen the economy of the develop homes and their families. The study shows that it should develop and support a set of incentives to facilitate investment in microenterprise development. For Christians, faith and obedience attract the Spirit and God’s blessing prosperity, the base is the spiritual foundations, and prosperity is a state of mind. It is a spiritual condition which is reflected in happiness and inner peace. Microfinance has a role in the development of family economies, fighting poverty and aims to eradicate it empowers women and usually there is a change of mentality in women and stop being dependent on the husband. There is a social impact on the people who carry out projects, helps very poor households meet basic needs, protect against risks, allows improved social and economic welfare of households, and promotes gender equity
Keywords: Savings; micro-entrepreneurship; family development; faith; obedience